2008
DOI: 10.1088/0953-4075/41/6/065503
|View full text |Cite
|
Sign up to set email alerts
|

Control of atomic entanglement by the dynamic Stark effect

Abstract: We study the entanglement properties of two three-level Rydberg atoms passing through a singlemode cavity. The interaction of an atom with the cavity field allows the atom to make a transition from the upper most (lower most) to the lower most (upper most) level by emission (absoprtion) of two photons via the middle level. We employ an effective Hamiltonian that describes the system with a Stark shifted two-photon atomic transition. We compute the entanglement of formation of the joint two-atom state as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…The resonant interaction of a field mode in excited states with two atoms has been investigated theoretically in [6][7][8] for simultaneous interaction and [9,10] for consecutive interaction, revealing wavepacket splitting, slow atomic state evolution, and collapse-revival dynamics of entanglement similar to those observed in one atomfield system. The off-resonant interaction of a field wave packet with two atoms was studied experimentally and theoretically in [11,12] as a means of measurement of the cavity decay rate and its effect on the dephasing of Schrödinger cat states.…”
Section: Introductionmentioning
confidence: 99%
“…The resonant interaction of a field mode in excited states with two atoms has been investigated theoretically in [6][7][8] for simultaneous interaction and [9,10] for consecutive interaction, revealing wavepacket splitting, slow atomic state evolution, and collapse-revival dynamics of entanglement similar to those observed in one atomfield system. The off-resonant interaction of a field wave packet with two atoms was studied experimentally and theoretically in [11,12] as a means of measurement of the cavity decay rate and its effect on the dephasing of Schrödinger cat states.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the problem of controlling entanglement by dynamic Stark effect has attracted much attention. [15−17] Ghosh et al [15] have found that the Stark shift can be used to enhance the magnitude of atomic entanglement. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, each atom in the system can be treated as an effective two-level system involving its |e, α and |g, α electronic states. This is done by means of an adiabatic elimination of the intermediate state [20,21] assuming that the initial states of the electron for the system include only the states |e, α and |g, α . The Hamiltonian describing such a system can be written in the interaction representation aŝ…”
Section: Phase Propertiesmentioning
confidence: 99%